Individual and interactive effects of product variables and process settings on selected quality parameters of heat-treated Calamansi juice - Tan, Athalie Kaye L.
This study established predictive models for the individual and interactive effects of various combinations of product variables and process settings namely heating temperature, heating time, soluble solids (SS), and titratable acidity (TA) on the residual ascorbic acid (AA) content, and ascorbic acid loss (ΔAA) of simulated citrus juice (SCJ) systems using Response Surface Methodology (RSM). Polynomial models describing the individual and interactive effects of temperature, time, SS and dilution rate on the Commission Internationale de l'Éclairage (CIE) color parameters of heat-treated calamansi juice were also established using RSM. SCJs and calamansi juice samples were prepared according to the combinations generated by the Central Composite Rotatable Design of Experiment. Only the individual and linear effects of temperature and time significantly (P<0.05) affected AA and ΔAA. The individual linear and quadratic effects of dilution rate significantly affected CIE L*, ΔL* values; while a*, Δa* values were significantly influenced by the linear and quadratic effects of temperature, SS and dilution rate. Furthermore, b*, Δb*, C*, and ΔC* were significantly affected by the individual linear and quadratic influences of SS and dilution rate, and the interaction of SS and dilution rate. Meanwhile, a significant lack of fit was found in the final models of CIE h°, Δh°, and ΔE* values. All validating systems for the predictive models for AA and ΔAA had acceptable predictive efficacy with accuracy factor (Af) ranging from 1.00 to 1.60. On the other hand, mathematical validation of the resulting models for the CIE color parameters showed that 112 out of 160 (70.00%) systems were predicted within the acceptable margin of error. The results reported in this work may be useful in the establishment of specific heat process schedules for unique products, for the preservation of product quality.